Species-specific imprint of the phytoplankton assemblage on carbon isotopes and the carbon cycle in Lake Kinneret, Israel. Issue 2 (1st January 2016) - Goodwin, Aram; Erez, Jonathan; Hambright, K. David; Koren, Nir; Barkan, Eugeni; Zohary, Tamar
Abstract: Lakes undergoing major changes in phytoplankton species composition are likely to undergo changes in carbon (C) cycling. In this study we used stable C isotopes to understand how the C cycle of Lake Kinneret, Israel, responded to documented changes in phytoplankton species composition. We compared the annual δ 13 C cycle of particulate organic matter from surface water (POMsurf ) between (1) years in which a massive spring bloom of the dinoflagellate Peridinium gatunense occurred ( Peridinium years) and (2) years in which it did not (non- Peridinium years). In non- Peridinium years, the spring δ 13 C–POMsurf maxima were lower by 3.3‰. These spring δ 13 C maxima were even lower in POM sinking into sediment traps and in zooplankton (lower by 6.8 and 6.9‰, respectively). These differences in the isotopic composition of the major organic C components in the lake represent ecosystem-level responses to the presence or absence of the key blooming species P. gatunense . When present, the intensive, almost monospecific bloom lowers the concentrations of CO2(aq), causing a reduction in the isotopic fractionation of the algae (higher δ 13 C of POMsurf ) and massive precipitation of calcium carbonate (CaCO3 ). In non- Peridinium years, the phytoplankton cannot deplete CO2(aq) to similar levels; the algae maintain higher isotopic fractionation, leading to lower δ 13 C maxima. These changes are reflected higher up in the food web (zooplankton) and in sedimenting organic matter. The consequences for the ecosystem in non- Peridinium years are lower export of both organic and inorganic C.